Evaluation of ICT Migration Plans in a Select Number of Companies in South Africa - Elegbeleye, Femi Abiodun; Elegbeleye, Ife Fortunate; Oguntona, Olusegun (Universitas Bina Darma, 2025)
The rapid evolution of the Information and Communication Technology (ICT) industry has made ICT migration a critical component for companies seeking to enhance productivity, efficiency, and competitiveness. However, migration often presents challenges, including high costs, system compatibility issues, cybersecurity risks, and employee resistance to change. This study evaluates the ICT migration plans of selected companies in South Africa, examining their strategies, challenges, and overall effectiveness. Using a mixed-methods approach, the research integrates qualitative and quantitative data collected through interviews, surveys, and document analysis. Companies are selected through purposive sampling to ensure diversity in industry, size, and ICT readiness. The study focuses on analyzing existing ICT infrastructure, identifying migration obstacles, assessing the success of implemented plans, and providing recommendations for improvement. Key assessment areas include cost-effectiveness, system scalability, cybersecurity measures, employee training, and post-migration performance. The findings of this study will contribute to the existing literature on ICT migration while offering practical insights for businesses aiming to implement or refine their migration strategies. Additionally, it will provide valuable recommendations for industries and IT professionals, facilitating smoother and more efficient ICT transitions in South Africa.